In vitro model of retinoblastoma derived tumor and stromal cells for tumor microenvironment (TME) studies - Emily Alefeld; André Haase; Dario Van Meenen; Bettina Budeus; Oliver Dräger; Natalia Miroschnikov; Saskia Ting; Deniz Kanber; Eva Biewald; Nikolaos Bechrakis; Nicole Dünker; Maike Anna Busch (Cell Death and Disease)
Abstract Retinoblastoma (RB) is an intraocular tumor arising from retinal cone progenitor cells affecting young children. In the last couple of years, RB treatment evolved towards eye preserving therapies. Therefore, investigating intratumoral differences and the RB tumor microenvironment (TME), regulating tumorigenesis and metastasis, is crucial. How RB cells and their TME are involved in tumor development needs to be elucidated using in vitro models including RB derived stromal cells. In the study presented, we established primary RB derived tumor and stromal cell cultures and compared them by RNAseq analysis to identify their gene expression signatures. RB tumor cells cultivated in serum containing medium were more differentiated compared to RB tumor cells grown in serum-free medium displaying a stem cell like phenotype. In addition, we identified differentially expressed genes for RB tumor and stromal derived cells. Furthermore, we immortalized cells of a RB1 mutated, MYCN amplified and trefoil factor family peptid 1 (TFF1) positive RB tumor and RB derived non-tumor stromal tissue. We characterized both immortalized cell lines using a human oncology proteome array, immunofluorescence staining of different markers and in vitro cell growth analyses. Tumor formation of the immortalized RB tumor cell line was investigated in a chicken chorioallantoic membrane (CAM) model. Our studies revealed that the RB stromal derived cell line comprises tumor associated macrophages (TAMs), glia and cancer associated fibroblasts (CAFs), we were able to successfully separate via magnetic cell separation (MACS). For co-cultivation studies, we established a 3D spheroid model with RB tumor and RB derived stromal cells. In summary, we established an in vitro model system to investigate the interaction of RB tumor cells with their TME. Our findings contribute to a better understanding of the relationship between RB tumor malignancy and its TME and will facilitate the development of effective treatment options for eye preserving therapies.